Longitudinal micro-computed tomography monitoring of progressive liver regeneration in a mouse model of partial hepatectomy. (August 2017) - Will, Olga M; Damm, Timo; Campbell, Graeme M; von Schönfells, Witigo; Açil, Yahya; Will, Marcus; Chalaris-Rissmann, Athena; Ayna, Mustafa; Drucker, Claudia; Glüer, Claus-Christian
The partial hepatectomy (PH) model is widely used to study liver regeneration. Currently, the extent of regeneration is analyzed by measuring the weight of the liver post-mortem or by magnetic resonance imaging. In this study we aimed to determine whether liver volume gain can be accurately measured using micro-computed tomography (microCT). Approximately 42% of the liver was removed by ligation in C57BL/6 N mice. Mice were divided into two study groups. In group 1 conventional characterization of liver hyperplasia was performed by weighing the liver post-mortem. In group 2, liver volume gain was determined by microCT volume estimation. MicroCT results showed equivalent regeneration rates compared with the conventional method without the need to mathematically determine initial liver weights before PH. This parameter is strongly influenced by the age, strain and sex of the mice. In addition non-invasive microCT determination of volume gain over multiple time-points using the same animal reduces the number of animals needing to be used (in line with the 3R principle of replacement, reduction and refinement).